A Garra rufa Care Breathing Relaxation (GC-BR) in measuring the level of comfort and complaints of itching in the elderly with Pruritus based on Kolcaba's Comfort Nursing Theory - Wimar Anugrah Romadhon; Ita Noviasari (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Objective: Pruritus in the elderly can have a negative impact on aspects of comfort and health in the elderly, especially the ability to carry out daily activities. The Garra rufa Care Breathing Relaxation (GC-BR) intervention is a combination of two interventions with micro massage performed by garra rufa fish and relaxation techniques which are useful as exfoliating dead skin, increasing blood circulation, eliminating bacteria. The purpose of this study is that the presence of GC-BR therapy can increase comfort and reduce itching complaints in the elderly with pruritus. Methods: Experimental research design with quasi-experimental methods. The sample size was 20 elderly pruritus consisting of 10 treatment groups and 10 control groups. Samples were taken by total sampling. The independent variable is GC-BR. The dependent variable is the level of comfort and itching complaints of the elderly Pruritus. The research instrument was the General Comfort Questionnaire to assess the comfort of the elderly with pruritus and the Numeric Rating Scale. The statistical test used the Wilcoxon Signed Rank Test and the Mann Whitney Test with a significance level of 0.05 Results: The results showed that there was an effect of GC-BR on the level of comfort (p=0.005) and itching complaints (p=0.004) in the treatment group. Whereas in the control group there was no effect on the results of the comfort level (p=0.096) and complaints of itching; (p=0.655). The results of the comparison stated that there were differences in the post-test comfort level (p = 0.003) and itching complaints (p = 0.031). Conclusion: GC-BR has a significant effect on the level of comfort and itching complaints in the elderly. Health services are expected to implement this non-pharmacological therapy so as to create geriatric health services that are increasingly professional and of high quality